Influence of Parameters of a Printing Plate on Photoluminescence of Nanophotonic Printed Elements of Novel Packaging - Olha Sarapulova; Valentyn Sherstiuk (Journal of Nanotechnology)
In order to produce nanophotonic elements for smart packaging, we investigated the influence of the parameters of screen and offset gravure printing plates on features of printed application of coatings with nanophotonic components and on parameters of their photoluminescence. To determine the dependence of luminescence intensity on the thickness of solid coating, we carried out the formation of nanophotonic solid surfaces by means of screen printing with different layer thickness on polypropylene film. The obtained analytical dependencies were used to confirm the explanation of the processes that occur during the fabrication of nanophotonic coverings with offset gravure printing plates. As a result of experimental studies, it was determined that the different character of the dependency of total luminescence intensity of nanophotonic elements from the percentage of a pad is explained by the use of different types of offset gravure printing plates, where the size of raster points remains constant in one case and changes in the other case, while the depth of the printing elements accordingly changes or remains constant. To obtain nanophotonic areas with predetermined photoluminescent properties, the influence of investigated factors on changes of photoluminescent properties of nanophotonic printed surfaces should be taken into consideration.